Exosomal circMACF1 drives PI3K/AKT/mTOR-mediated autophagy suppression in laryngeal squamous cell carcinoma: circMACF1 drives PI3K/AKT/mTOR in LSCC - Zhu, Yingnan; Duan, Chuanxin; Gui, Yunzhi; Chen, Danxia; Su, Xi (Cellular and Molecular Biology, 2024)
Laryngeal squamous cell carcinoma (LSCC) is a common malignant tumor. The regulatory functions of circular RNAs (circRNAs) in cancers have been broadly reported. The hsa_circ_0011773 (circMACF1) is reported to be overexpressed in LSCC tissues, while its biological function in LSCC remains unclear. CircMACF1 expression in LSCC tissues and cells was assessed via RT-qPCR. Exosomes extracted from cells were identified by TEM and NTA. Autophagy-related proteins were tested by western blot. Confocal microscope was employed for analyzing LC3 expression. Cell proliferation, migration, and invasion were assessed by CCK-8 assay and transwell assay. The levels of main proteins on PI3K/AKT/mTOR were tested by western blot. We observed that circMACF1 was highly expressed in LSCC tissues and cells. Furthermore, circMACF1 expression was also upregulated in the exosomes derived from LSCC cells. CircMACF1 depletion promoted LC3 expression in cells. Additionally, we proved that circMACF1 knockdown suppressed LSCC cell proliferative, migratory and invasive capabilities via promoting autophagy. Exosomal circMACF1 was found to promote LSCC tumor growth. Then, we proved that circMACF1 could activate PI3K/AKT/mTOR pathway to regulate autophagy. Moreover, MACF1 was positively regulated by circMACF1 and its overexpression notably reversed the effects of circMACF1 depletion in LSCC progression. Exosomal circMACF1 can regulate PI3K/AKT/mTOR-mediated autophagy suppression to facilitate LSCC development.